FRI0140 Restarting Biologics in Patients Who Developed Tuberculosis During Anti TNF-Alpha Treatment. (9th June 2015) - Ozguler, Y.; Hatemi, G.; Ugurlu, S.; Seyahi, E.; Melikoglu, M.; Borekci, S.; Ongen, G.; Hamuryudan, V.
Abstract : Background: The use of TNF-alpha inhibitors is associated with an increased risk of tuberculosis (TB) and all guidelines recommend discontinuation of TNF-alpha inhibitors if active TB develops. However discontinuation of treatment can result in flare of the underlying disease and there is fairly limited data about the safety of re-administration of biologics. Objectives: To determine the safety of re-administration of biologic agents in patients who had developed active TB during anti TNF-alpha treatment. Methods: The charts of 21 patients (11 men, 10 women; mean age 38.4±13.2 SD years and mean disease duration 10.6±7.8 SD years at the time of TB development) who developed active TB (8 pulmonary, 13 extrapulmonary) during anti TNF-alpha treatment (15 with infliximab, 3 with adalimumab and 3 with etanercept) in our clinic between 2001 and 2013 were reviewed retrospectively. Patients were invited to the clinic if their current status was not known. The mean follow-up between re-administration of biologics and the end of our survey was 38.1±28.5 SD months. Results: Among the 21 patients who developed TB during anti TNF-alpha treatment, 1 patient with miliary TB died during the first month of anti-TB treatment. A biologic agent was restarted in 15 of the 20 remaining patients (75%). The first re-administrated biologic agent was etanercept in 6 patients (4 AS, 1 RA, 1 Behçet's syndrome), adalimumab in 1 AS patient, golimumab in 1 AS patient, rituximab in 5 patients (4 RA, 1 Takayasu), and interferon-alpha in 2 Behçet's patients. Biologic treatment was reinitiated while anti-TB treatment was ongoing in 3 patients (etanercept in 1 Behçet's patient at month 3, rituximab in 2 RA patients at month 4), and a median of 3.5 months (IQR: 0.6-22.2 months) after the completion of anti TB treatment in 12 patients. In 6 patients treatment was switched to another biologic (infliximab, adalimumab, golimumab, abatacept, rituximab and canakinumab in 1 patient each) due to lack of efficacy. One of these 15 patients developed TB again and another patient died with gastric cancer. The patient who developed TB again was a Behçet's patient who had initially used infliximab. He had developed pulmonary TB on the 18th month of infliximab and infliximab was stopped. At the third month of anti TB treatment, etanercept was started due to severe sight-threatening uveitis and anti-TB treatment was completed to 6 months. Etanercept was continued for 15 months and then was replaced with canakinumab due to inadequate response. He developed tuberculous meningitis while receiving the 3rd dose of canakinumab in combination with methotrexate, cyclosporine and steroids. He received another 9 months of anti-TB treatment and is currently stable on IFN-alpha therapy for 16 months. Conclusions: Biologic agents, including TNF-alpha antagonists, can be reinitiated in patients who had previously developed TB under anti TNF treatment. Careful follow-up for TB reinfection is required. Disclosure of Interest: None declared